Feasibility Study of CHEAP: Digital Marketing App for Collaborative Batik MSMEs and Religious Sites - R Kurniawan Dwi Septiady; Alfa Yuliana Dewi (Universitas Muhammadiyah Semarang, 2025)
This study investigates the feasibility of the CHEAP (